Synchronized proinsulin trafficking reveals delayed Golgi export accompanies β-cell secretory dysfunction in rodent models of hyperglycemia - Cierra K. Boyer; Casey J. Bauchle; Jianchao Zhang; Yanzhuang Wang; Samuel B. Stephens (Scientific Reports, 2023)
Abstract The pancreatic islet β-cell’s preference for release of newly synthesized insulin requires careful coordination of insulin exocytosis with sufficient insulin granule production to ensure that insulin stores exceed peripheral demands for glucose homeostasis. Thus, the cellular mechanisms regulating insulin granule production are critical to maintaining β-cell function. In this report, we utilized the synchronous protein trafficking system, RUSH, in primary β-cells to evaluate proinsulin transit through the secretory pathway leading to insulin granule formation. We demonstrate that the trafficking, processing, and secretion of the proinsulin RUSH reporter, proCpepRUSH, are consistent with current models of insulin maturation and release. Using both a rodent dietary and genetic model of hyperglycemia and β-cell dysfunction, we show that proinsulin trafficking is impeded at the Golgi and coincides with the decreased appearance of nascent insulin granules at the plasma membrane. Ultrastructural analysis of β-cells from diabetic leptin receptor deficient mice revealed gross morphological changes in Golgi structure, including shortened and swollen cisternae, and partial Golgi vesiculation, which are consistent with defects in secretory protein export. Collectively, this work highlights the utility of the proCpepRUSH reporter in studying proinsulin trafficking dynamics and suggests that altered Golgi export function contributes to β-cell secretory defects in the pathogenesis of Type 2 diabetes.